The Cambridge handbook of personality disorders - Lejuez, Carl W.; Gratz, Kim L. (UK Cambridge University Press, 2020)
"This Handbook provides both breadth and depth regarding current approaches to the understanding, assessment, and treatment of personality disorders. The five parts of the book address etiology; models; individual disorders and clusters; assessment; and treatment. A comprehensive picture of personality pathology is supplied that acknowledges the contributions and missteps of the past, identifies the crucial questions of the present, and sets a course for the future. It also follows the changes the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) has triggered in the field of personality disorders. The editors take a unique approach where all chapters include two commentaries by experts in the field, as well as an author rejoinder. This approach engages multiple perspectives and an exchange of ideas. It is the ideal resource for researchers and treatment providers at all career stages"--
Neuroimaging in personality disorders / Chi C. Chan, Daniel H. Vaccaro, Nina L .J. Rose, Laura E. Kessler, Erin A. Hazlett -- Issues and new directions in personality disorder genetics / Kerry L. Jang and Fiona Choi -- Environmental and sociocultural influences on personality disorders / Brianna J. Turner, Julie Prud'homme, and Nicole Legg -- Personality pathology in youth / Carla Sharp and Barbara De Clercq -- Controversies in the classification and diagnosis of personality disorders / Joel Paris -- Categorical models of personality disorders / Igor Weinberg -- The five-factor model of personality disorders / Joshua D. Miller and Thomas A. Widiger -- Interpersonal models of personality pathology / Michael J. Roche and Emily B. Ansell -- Cluster a personality disorders / John G. Kerns -- Borderline personality disorder / Alexander L. Chapman, Nora H. Hope, and Brianna J. Turner -- An integrative biobehavioral trait perspective on antisocial personality disorder and psychopathy / Sarah J. Brislin and Christopher J. Patrick -- Narcissistic and histrionic personality disorders / Aaron L. Pincus, Sindes Dawood, Leila Z. Wu, and Chloe F. Bliton -- Cluster C anxious-fearful personality pathology and avoidance / Charles A. Sanislow and Anna Darre Hector -- Methods and current issues in dimensional assessments of personality pathology / Chloe M. Evans, Trevor F. Williams, and Leonard J. Simms -- Categorical assessment of personality disorders : considerations of reliability and validity / Janine D. Flory -- Assessment of mechanisms in personality disorders / Sheila E. Crowell, Parisa R. Kaliush, and Robert D. Vlisides-Henry -- Cognitive behavioral approaches / M. Zachary Rosenthal, Kristin P. Wyatt, and Kibby McMahon -- Psychoanalytic/psychodynamic approaches to personality disorders / Peter Fonagy, Anthony Bateman, Patrick Luyten, Elizabeth Allison, and Chloe Campbell -- Using DSM-5 and ICD-11 Personality traits in clinical treatment / Bo Bach and Jennifer Presnall-Shvorin -- Brief therapeutic approaches for personality disorders / Katherine L. Dixon-Gordon, Lindsey C. Conkey, and Sherry E. Woods -- Recent developments in the pharmacologic management of personality disorders / Paul S. Links, Philippe Boursiquot, and Madison Links.
Includes bibliographical references and index.
Keywords: Personality disorders -- Handbooks, manuals, etc